Meningkatkan Kesadaran Pencegahan Penyakit Tidak Menular pada Hipertensi dan Diabetes Melitus melalui Edukasi di Masyarakat - Uta Provinsiana Sukmara (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Hypertension and Diabetes Mellitus (DM) are the most common diseases and have become major public health problems throughout the world, and Indonesia is no exception. Hypertension and diabetes mellitus are two major non-communicable diseases whose prevalence continues to increase globally and nationally. Lack of awareness and low health literacy are one of the main causes of delays in diagnosis and control of this disease, especially in rural areas. This community service was held in Kaliwanglu Kulon Village, Pakem District, Sleman Regency, Special Region of Yogyakarta, on May 1, 2025. This activity involved 45 participants from villagers, with the main focus being on providing health education and checking blood pressure and blood sugar at any time. Educational activities include material on definitions, risk factors, symptoms, complications, and strategies for the prevention and management of hypertension and diabetes. The screening results showed that 40% of participants had high blood pressure and 31% had blood sugar when it was above normal limits. This activity succeeded in increasing citizen knowledge and became an important early intervention in community-based non-communicable disease promotion and prevention.